Competency Model at Global Line Limited (GLL): A Case Study - Joshi, Gowri Vidyanand; Pande, Sharon (Prabandhan: Indian Journal of Management, 2013)
This case study is about an Indian media organization - Global Line Limited (GLL) that had a very robust Human Resource function. The HR department of GLL recently introduced a competency model that measures 44 different competencies for potential recruits. The competencies had been categorized into skills, knowledge, and talent. The head of the HR department was convinced that the competency based selection process was working positively for them until a young professional named Suman was hired in the talent acquisition team of the department. Suman collected feedback from line managers, analyzed the process, and tried to identify ways to further improve the system. The significant learning from this case is that HR departments of business organizations must innovate and must be proactive in implementing the latest HR technologies. However, the practical applicability of the model must be kept in mind while framing any HR model. Furthermore, the HR should always stay connected with the pulse of the workforce to ascertain whether or not the function is adding adequate value to business outcomes.